Translational Research Studies Unraveling the Origins of Psoriatic Arthritis: Moving Beyond Skin and Joints - Bolt, Janne W.; van Ansenwoude, Chaja M. J.; Hammoura, Ihsan; van de Sande, Marleen G.; van Baarsen, Lisa G. M. (Frontiers in Medicine, 2021)
Patients with psoriatic arthritis (PsA) suffer from decreased quality of life despite available treatments. In the latest years, novel therapies targeting IL-17/IL-23 and TNF pathways improved clinical outcome. Despite this, remission of disease is frequently not achieved, continuous treatment is often required to reach clinical remission, and prevention of PsA in psoriasis (PsO) patients is currently impossible. Better understanding of PsA pathogenesis is required to develop novel treatment strategies that target inflammation and destruction more effectively and at early stages of the disease, or before clinically manifest disease. The skin is considered as one of the sites of onset of immune activation, triggering the inflammatory cascade in PsA. PsO develops into PsA in 30% of the PsO patients. Influenced by environmental and genetic factors, the inflammatory process in the skin, entheses and/or gut may evolve into synovial tissue inflammation, characterized by influx of immune cells. The exact role of the innate and adaptive immune cells in disease pathogenesis is not completely known. The involvement of activated IL-17A+ T cells could implicate early immunomodulatory events generated in lymphoid organs thereby shaping the pathogenic inflammatory response leading to disease. In this perspective article, we provide the reader with an overview of the current literature regarding the immunological changes observed during the earliest stages of PsA. Moreover, we will postulate future areas of translational research aimed at increasing our knowledge on the molecular mechanisms driving disease development, which will aid the identification of novel potential therapeutic targets to limit the progression of PsA.